Multi-epoch very long baseline interferometric observations of the nuclear starburst region of NGC 253: Improved modelling of the supernova and star-formation rates - Rampadarath, Hayden; Morgan, John; Lenc, E.; Tingay, Steven (IOP, 2014)
The results of multi-epoch observations of the southern starburst galaxy, NGC 253, with the Australian Long Baseline Array (LBA) at 2.3 GHz are presented. As with previous radio interferometric observations of this galaxy, no new sources were discovered. By combining the results of this survey with Very Large Array observations at higher frequencies from the literature, spectra were derived and a free-free absorption model was fitted of 20 known sources in NGC 253. The results were found to be consistent with previous studies. The supernova remnant, 5.48−43.3, was imaged with the highest sensitivity and resolution to date, revealing a two-lobed morphology. Comparisons with previous observations of similar resolution give an upper limit of 104 km s−1 for the expansion speed of this remnant. We derive a supernova rate of <0.2 yr−1 for the inner 300 pc using a model that improves on previous methods by incorporating an improved radio supernova peak luminosity distribution and by making use of multi-wavelength radio data spanning 21 years. A star formation rate of SFR(M ≥ 5 M) < 4.9 M yr−1 was also estimated using the standard relation between supernova and star-formation rates. Our improved estimates of supernova and star-formation rates are consistent with studies at other wavelengths. The results of our study point to the possible existence of a small population of undetected supernova remnants, suggesting a low rate of radio supernovae production in NGC 253.